Indian camps circumvented Raton - Pappas, Mike (Raton, NM Raton Range, 1989)
Columns written by Mike Pappas, owner of the Sweet Shop Restaurant, for the Raton Daily Range on a wide variety of topics, some historical, some current, some personal.
Newspaper Article by Mike Pappas
Master list item #: 19
File location is in the Raton File Cabinet
Keywords: Dunning, Clara; Salomon, Julian; Kaniache; Lloyd, Betty; Carson, Kit; Walsen, Fred; Raton Range; Civil War; Local History; Native Americans; Utes Indians; 3rd U.S. Cavalry; Mouhaches and Company A; Trinidad, Colorado; Ute Creek; Ute Park; Ute Mountains; Ute Springs; Taos County; Colfax County; Cuchara Pass; Cimarron, New Mexico; The Plaza de Leones (Walsenburg)